Peningkatan Sertifikasi Pangan pada UMKM Sale Pisang Khas Majenang untuk Meningkatkan Kualitas dan Daya Saing Produk - Widya Pratiwi; Johar Alimuddin; Ahmad Arifin Zain (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Most producers of Sale Pisang (traditional dried banana) from Majenang have not yet obtained a Home Industry Food Production Certificate (PIRT), which is an essential requirement for improving product quality and legal compliance in the food sector. The Home Industry Food Production Certification Training aims to enhance the understanding of business owners regarding the importance of business legality, particularly the PIRT number, and to provide knowledge on production feasibility, product development, as well as strategies to increase production frequency and market reach. The activity was carried out through educational sessions and guidance in the PIRT application process. Evaluation results show an 87% increase in participants' understanding of the training materials. Additionally, business owners who previously did not have PIRT have begun completing the necessary requirements to obtain the certification. Thus, this training effectively increased the awareness and capability of UMKM actors in running safe, high-quality businesses that comply with existing standards